LEARNING INNOVATION TRAINING BASED ON TUTORING APPLICATION AND VILLAGE PROFILE IN SUMBERAGUNG VILLAGE, NGANTANG DISTRICT, MALANG REGENCY - Abdul Basid; Lilik Nur Kholidah; Titis Thoriquttyas; Moh. Fauzan; Jihad Hamas Dawenan; Khusnul Hitmah Al Adawiyah (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2022)
Tutoring is an informal activity that aims to help students to be able to solve problems of learning difficulties at school or additional learning that is tailored to the needs of students carried out by an institution/individual. Tutoring is also considered very effective because teachers in tutoring will pay attention to students' understanding and development of the subjects that have been studied. In this service, we will conduct tutoring in Sumberagung Village. This community service activity aims to help the learning process of elementary and junior high school students who have problems completing schoolwork or others. The result of this training is that the elementary and junior high school students will be skilled and accustomed to solving problems that are considered problematic in each task independently. Another result is that to introduce the potential in Sumberagung Village; it is necessary to have a media that can document the village's potential. To overcome these problems, a village profile video in this community service activity will be made, which includes the potential of the village in Sumberagung Village. The video shows the potential in Sumberagung Village, including batik, coffee and milk.